Makna Lingkungan Hidup di Masa Sriwijaya: Analisis Isi pada Prasasti Talang Tuwo - Yenrizal Yenrizal (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The purpose of this study is to understand the interpretation of the environmental aspects during the Sriwijaya kingdom  in  the  7th  century.  The interpretation  is  based  on  text  written  on  the  script  of  the Prasasti  Talang  Tuwo  (Talang  Tuwo  inscription),  the  one  and  only  inscription  talking  about  the environmental  arrangement.  This  study  deploys  a  discourse  analysis  by  Mangineau which  discusses  the discourse  from  three  aspects:  content,  process,  and  emergence.  Data are analyzed by qualitative  method using  environmental  communication  perspective.  This  study  indicates  that (a)  the  social  situation  in Sriwijaya’s  era  had  determined  the  environmental  interpretation;  (b) the  process  occurred  shows  social context playing significant role, and (c) it shows how this process was taking place in certain stages.